A Comparative Anatomical Study of the Grapevine Shoot: I Epidermis - Swanepoel, J. J.; De La Harpe, A. C.; Orffer, C. J. (South African Journal of Enology and Viticulture, 2017)
Material gathered from three positions on the shoot and cane during veraison and two weeks after harvest were investigated for taxonomic features concerning the epidermis. Stomata and lenticels were present in all the cultivars studied, but trichomes were frequently present only on 99 Richter. Based on epidermal characteristics a dendogram giving the percentage similarity between cultivars, was constructed, and from this was concluded that concerning taxonomic features on Vitis vinifera L. cultivars tend to have a more than 90% similarity irrespective of the position on the shoot.